The Prediction of Technical Change - Gilfillan, S. Colum (The Review of Economics and Statistics, 1952)
PREDICTION usually requires counting, dating, and measuring, and so plunges us at once into semantics, the perpetual bugbear of statistics, the endemic disease that more or less infects all our figures. For statistics begins with counting, and counting begins with definition of the thing to be counted -and inventions can hardly be defined. Patents are not quite so bad, and we shall take them up later. Inventions, like many things and notably people, don't stay the same, but are perpetually evolving, growing, squirming out of their definitions. You may have heard of the Irishman who complained that his pig wouldn't stay counted. That is supposed to be a joke on the Irishman; but he was dead right it was the pig that was false and unstatistical. For that pig began as a little shoat, and ate and grew night and day until he became a 5oo-pound hog, a creature utterly different in every pertinent aspect from the little suckling piglet. So he couldn't stay counted Similarly in invention, suppose we consider television. That sounds simple, since we all know what television is. Or do we? Was it already television in I847 when Souvestre satirically predicted it? Or did it begin in I877 when the first apparatus was built, or in I882 when the scanning disk was added, or in I9OI when Fessenden designed a wireless system? Or was it Zworykin's modern cathode ray receiver of I929 that constituted the invention of television, with the kinescope, and some experimental broadcasts the next year? Or is our date I928 or I937 when regular broadcasting began? Or should it be some future date when with color, three-dimensional vision, binaural hearing, and worthy programs, the art will at last enter the prodigious destiny of the home theater? And is this television, at whatever stage, to be counted always as invention? If so, our statistics mean no more than that one pig. Definition of invention